The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/pcr2.10216
|View full text |Cite
|
Sign up to set email alerts
|

The crystallization ofPA11,PA12, and their random copolymers at increasing supercooling: From eutectic segregation to mesomorphic solid solutions

Abstract: The non-isothermal and isothermal crystallization of polyamide 11 (PA11), polyamide 12 (PA12), and their random copolymers was studied over the entire temperature range between the glass transition temperature and the high temperature melting point, using differential scanning calorimetry (DSC) and fast scanning calorimetry (FSC). The DSC and FSC thermal behavior was translated into structural evolutions, relying on earlier gathered X-ray based structural information and theoretical calculations. At low superc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 46 publications
(152 reference statements)
0
25
0
Order By: Relevance
“…Most of the high-temperature crystallization rate minima in polymers have been found at the transition between two polymorphic phases. In addition to our work on precision polyethylenes with halogens and long-spaced polyacetals, minima have been found in polyamides, , polyesters, polyketones, syndiotactic polystyrene, isotactic polypropylenes, , dendron-like giant molecules, and amphiphilic molecular brushes of poly­(ethylene oxide) and n -alkyl side chains . Minima that appear in the low-temperature region approaching the glass transition have been interpreted as a change from heterogeneous to homogeneous nucleation. …”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Most of the high-temperature crystallization rate minima in polymers have been found at the transition between two polymorphic phases. In addition to our work on precision polyethylenes with halogens and long-spaced polyacetals, minima have been found in polyamides, , polyesters, polyketones, syndiotactic polystyrene, isotactic polypropylenes, , dendron-like giant molecules, and amphiphilic molecular brushes of poly­(ethylene oxide) and n -alkyl side chains . Minima that appear in the low-temperature region approaching the glass transition have been interpreted as a change from heterogeneous to homogeneous nucleation. …”
Section: Introductionmentioning
confidence: 70%
“…Prior rate minima or discontinuities found in the temperature gradient of the crystallization rate of precision polyethylenes and in other semicrystalline polymers have been invariably associated with a polymorphic transition. , The minima displayed by PEBs in Figure are of interest because PEB does not undergo any apparent polymorphic transition in the whole range of T c analyzed. Such continuous isomorphic behavior and the characteristics of the rate minima, namely a temperature gradient that becomes positive approaching the melting point of a thinner metastable crystal structure, are equivalent to the minimum of the crystallization rate found in long-chain n -alkanes by Ungar and Keller. …”
Section: Resultsmentioning
confidence: 99%
“…47 The T m of the as-received endcapped PA12 is rather low for laterally extended 5 repeating unit thick lamellar but too high to be due to 4 repeating unit thick crystals, of which the predicted T m by Verkinderen et al is 175.6 °C. 46 Therefore, endcapped PA12 seems to contain 5 repeating unit thick crystals with limited lateral dimensions. 46 After melting and cooling at 10 °C/min, the crystals are only 4 repeating units thick, judging from the melting peak temperature in the second heating run, reducing the crystal thickness to 61.5 Å.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Based on the advanced thermal analysis system (ATHAS) databank and literatures, the T 0 m for PA12 is recommended to be 267 C (500 K). 33,34 Based on Equation (3), the f local exhibits two local minima as a function of ψ, which are observed in Figure 2. It is observed that the trend of the free local energy density differs with temperature.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Hence, with polyamides experiencing lamellar thinning during crystallization, 32 the Hoffman‐Weeks relation is not suitable for determining the equilibrium melting temperature for PA12. Based on the advanced thermal analysis system (ATHAS) databank and literatures, the Tm0 for PA12 is recommended to be 267°C (500 K) 33,34 …”
Section: Mathematical Modelmentioning
confidence: 99%